A perovskite material and its preparation method and application
By adding lead chloride and formamidine chloride to the perovskite film to form the mesophase FAPbCl3, the particle size and roughness of the two-dimensional perovskite film are solved, and the photoelectric conversion efficiency of perovskite solar cells is improved.
Patent Information
- Application Number
- CN202310482605.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-28
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-04-28
AI Technical Summary
The existing two-dimensional perovskite films have small crystal particle sizes and large film roughness, resulting in low photoelectric conversion efficiency of perovskite solar cells.
Lead chloride and formidine chloride are used as additives to form the mesophase FAPbCl3, which delays the crystallization rate of two-dimensional perovskites, increases the crystal particle size of the perovskite film and reduces the roughness of the film.
The crystallinity and crystallization orientation of the perovskite film are improved, the surface defects are reduced, the grain size is increased, and the maximum photoelectric conversion efficiency is reached 16.31%.
Smart Images

Figure CN116568104B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of optoelectronic functional materials and devices, and in particular, to a perovskite material and a preparation method and application thereof. Background Art
[0002] In recent years, ABX3-type materials with perovskite structure have made great progress in the photovoltaic field. The photoelectric conversion efficiency has increased from the initial 3.8% to the current maximum of 25.7%, which is gradually approaching the photoelectric conversion efficiency of silicon-based photovoltaic materials. In addition, the raw materials of perovskite materials are widely available and inexpensive, which facilitates large-scale continuous production and has low production costs. Therefore, solar cells based on perovskite photovoltaic materials have great application prospects.
[0003] However, existing perovskites are easily decomposed under the induction of water and oxygen, and their structure will be destroyed, which will cause them to partially or completely lose their photoelectric effect. The two-dimensional perovskite materials formed using organic molecules as ligands have good hydrophobicity and therefore have higher structural stability. However, the films currently prepared using two-dimensional perovskite materials still have small particle size, large roughness, and many defects on the film surface, which in turn leads to low photoelectric conversion efficiency of perovskite solar cells.
[0004] The prior art discloses a formamidine-based two-dimensional perovskite film and its preparation method and application, wherein a linear organic diamine is selected as a spacer cation to form a quasi-two-dimensional perovskite (C x H 2x (NH3)2)(CH(NH2)2) n-1 Pb n I 3n+1 The film can be prepared by changing the solvent ratio and the anti-solvent addition time in the preparation process to control the crystal quality of the perovskite film. However, the photoelectric conversion efficiency of the perovskite film prepared by the prior art can only reach 11.43% at most, and the most important factor affecting the photoelectric conversion efficiency of the perovskite film in the prior art is the crystal quality of the perovskite film, and the two most important factors affecting the crystal quality are the crystal particle size and the film roughness. It can be seen that the crystal particle size and the film roughness of the two-dimensional perovskite film prepared by the prior art still need to be improved. Summary of the invention
[0005] In order to solve the problems of small crystal grain size and large film roughness of existing two-dimensional perovskite films, the present invention provides a method for preparing perovskite materials, using lead chloride and formamidine chloride as additives to form an intermediate phase FAPbCl3, which slows down the crystallization rate of the two-dimensional perovskite, increases the crystal grain size of the perovskite film, and reduces the roughness of the film.
[0006] Another object of the present invention is to provide a perovskite material.
[0007] Another object of the present invention is to provide an application of a perovskite material in a perovskite solar cell.
[0008] Another object of the present invention is to provide a perovskite solar cell.
[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0010] A method for preparing a perovskite material comprises the following steps:
[0011] S1. The organic amine hydroiodide, formamidine iodide and lead iodide are added to an organic solvent and mixed thoroughly, and then formamidine chloride and lead chloride are added as additives, and mixed thoroughly to obtain a perovskite precursor solution;
[0012] S2. coating the perovskite precursor solution obtained in step S1 onto a substrate and annealing to form a perovskite material;
[0013] In step S1, the molar ratio of formamidine chloride to lead iodide is (0.06-0.15):1, and the molar ratio of formamidine chloride to lead chloride is (1-4):1.
[0014] The molecular formula of the perovskite material constructed by organic amine hydroiodide, formamidine iodide (FAI) and lead iodide (PbI2) is (C x H 2x (NH3)2)(CH(NH2)2) n-1 Pb n I 3n+1 or (C x H 2x NH3)(CH(NH2)2) n-1 Pb n I 3n+1 In a specific embodiment of the present invention, n can be any integer between 3 and 10 (e.g., 3, 4, 5, 6, 7, 8, 9, 10), and x is the carbon number of the alkyl group in the organic amine hydroiodide, which can be any integer between 2 and 8 (e.g., 2, 3, 4, 5, 6, 7, 8).
[0015] By mixing formamidine iodide and lead iodide, a perovskite octahedron with the molecular formula FAPbI3 can be prepared. The octahedrons can be interconnected through iodide ion sites to form a periodic three-dimensional structure. When the system contains organic amine hydroiodide, the organic amine cations can be inserted into the three-dimensional perovskite structure as a spacer layer, cutting the three-dimensional perovskite into a perovskite material with a two-dimensional layered structure. The perovskite between the two layers of organic amine cation spacer layers is a layer, and the perovskite layer contains a sublayer composed of perovskite octahedrons.
[0016] Towards perovskite materials with two-dimensional layered structures (C x H 2x (NH3)2)(CH(NH2)2) n-1 Pb n I 3n+1 or (C x H 2x (NH3))(CH(NH2)2) n-1 Pb n I 3n+1Adding two additives, formamidine chloride (FACl) and lead chloride (PbCl2), can increase the crystal size of the perovskite material and reduce the roughness of the perovskite two-dimensional film. Specifically, when FACl and PbCl2 are added to the system at the same time, an intermediate phase FAPbCl3 can be formed, and the formation of the intermediate phase inhibits the formation of low-n value phases and yellow δ phases in the perovskite. n is the number of perovskite octahedral sublayers in the perovskite layer between the two layers of organic ligands in the perovskite material, and one layer of perovskite octahedron constitutes one sublayer. The crystal orientation of the n-layer perovskite octahedral sublayers between the two layers of organic ligands is consistent, but when separated by the organic ligand layer, the two perovskite layers with n-layer perovskite octahedral sublayers do not necessarily have a consistent crystal orientation. Referring to the concept of magnetic domains in a magnetic field, the smaller the magnetic domain, the smaller the orientation specificity of different magnetic domains under the same magnetic field. Therefore, when the total number of octahedral sublayers in the perovskite material is the same, when the number of perovskite octahedral sublayers n between the two organic ligand layers in the perovskite material is smaller, the crystal orientation specificity inside the perovskite crystal is lower. Therefore, inhibiting the formation of low n value phases in the system can improve the crystal orientation specificity of the perovskite film, and the increase in crystal orientation specificity means that the roughness of the perovskite film can be reduced. Adding FACl and PbCl2 to the system at the same time can also inhibit the formation of the yellow δ phase, which is non-photoactive and not conducive to the improvement of the photoelectric conversion efficiency of the perovskite film. After inhibiting the formation of low n value phases and yellow δ phases, the two additives can slow down the crystallization rate of the perovskite material, thereby enabling the crystal to grow fully and increase the particle size of the perovskite crystal. The increase in particle size means that there are fewer grain boundaries inside the same volume of perovskite material, and the probability of photogenerated carriers being captured by grain boundary defects when transmitting in the perovskite is also lower, so the photoelectric conversion efficiency of the perovskite is improved.
[0017] The molar ratio of formamidine chloride to lead iodide in step S1 is controlled to (0.06-0.15):1 because when the molar ratio of formamidine chloride to lead iodide in the system is higher than 0.15:1, it is not conducive to the crystallization of perovskite, and the short-circuit current of the perovskite material is too small, which is not suitable for preparing perovskite solar cells; and when the molar ratio of formamidine chloride to lead iodide is lower than 0.06:1, it is difficult for formamidine chloride to improve the crystallization performance of the perovskite material.
[0018] The ratio of the amount of formamidine chloride to lead chloride in step S1 is controlled to (1-4):1, in order to control the formation of a complete intermediate phase FAPbCl3 in the perovskite system, thereby improving the crystallinity and orientation specificity of the perovskite, increasing the crystal grain size in the perovskite material and reducing the roughness of the perovskite film. When the ratio of the amount of formamidine chloride to lead chloride is lower than 1:1, too much lead chloride is added to the perovskite system and cannot be fully utilized, which easily induces the formation of a yellow δ phase; when the ratio of the amount of formamidine chloride to lead chloride is higher than 4:1, too much formamidine chloride is present in the perovskite system, which is not conducive to the crystallization of the perovskite.
[0019] When the amount ratio of formamidine chloride to lead iodide in step S1 is controlled to (0.06-0.15):1 and the amount ratio of formamidine chloride to lead chloride in step S1 is controlled to (1-4):1, the amount ratio of lead chloride to iodine chloride is (0.015-0.15):1.
[0020] In a specific embodiment of the present invention, the organic amine hydroiodide can be a hydroiodide of a linear alkylamine or a linear alkyldiamine. After the hydroiodide of the linear alkylamine or the linear alkyldiamine is added to the reaction system of formamidine iodide and lead iodide, the molar ratio of the salt to formamidine iodide and lead iodide can be controlled to be 1:(n-1):n, wherein n is any integer between 3 and 10 (for example, 3, 4, 5, 6, 7, 8, 9, 10), thereby preparing a perovskite material with a two-dimensional layered structure.
[0021] There are two types of structures of two-dimensional layered perovskite materials: Dion-Jacobson (DJ) type and Ruddlesden-Popper (RP) type. The RP type perovskite can be constructed by using the hydroiodide of linear alkylamines, while the DJ type perovskite can be constructed by using the hydroiodide of linear alkyldiamines, because the linear alkyldiamines have a quaternary ammonium cation at each end, which can form ionic bonds with the iodine anions in the two layers of perovskite octahedrons, separating the two layers of perovskites while eliminating the intermolecular forces between the two layers of perovskites. The carbon number of the linear alkyl in the organic amine hydroiodide can be any integer between 2 and 8 (e.g., 2, 3, 4, 5, 6, 7, 8).
[0022] In a specific embodiment of the present invention, the annealing in step S2 may be performed at 120° C. for 10 min.
[0023] Preferably, in step S1, the molar ratio of formamidine chloride to lead chloride is 2:1.
[0024] When the molar ratio of formamidine chloride to lead chloride is 2:1, the perovskite crystal has a greater crystallinity, because less lead chloride remains in the system after formamidine chloride and lead chloride form an intermediate phase. When there is more lead chloride remaining, it is easy to induce the formation of non-photoactive δ phase in the perovskite, reduce the crystallinity of the perovskite, and then reduce the size of the perovskite crystal particle size, while increasing the possibility of inconsistent grain orientation, thereby increasing the roughness of the perovskite film.
[0025] Preferably, in step S1, the molar ratio of lead chloride to lead iodide is (0.025-0.08):1.
[0026] The reason for optimizing the ratio of the amount of lead chloride to lead iodide is that when the ratio of the amount of lead chloride to lead iodide in the perovskite material is higher than 0.08:1, the excess lead chloride in the system will induce the appearance of a yellow delta phase in the perovskite material, reduce the crystallinity of the perovskite, and then reduce the size of the grains in the perovskite film. In addition, lead chloride is a non-photoactive substance, which will affect the photoelectric conversion efficiency of the perovskite. When the ratio of the amount of lead chloride to lead iodide is lower than 0.025:1, the content of lead chloride is too low, and it is difficult to improve the crystallization performance of the perovskite material.
[0027] Preferably, in step S1, the molar ratio of formamidine chloride to lead iodide is 0.1:1.
[0028] When the molar ratio of formamidine chloride to lead iodide is 0.1:1, the particle size of the perovskite crystal is larger.
[0029] Preferably, the organic amine hydroiodide in step S1 is a hydroiodide of a linear alkyl diamine.
[0030] When the organic amine hydroiodide is the hydroiodide of a linear alkyl diamine, the perovskite material has a two-dimensional DJ-type structure, and the preparation method of the perovskite material provided by the present invention has a better effect of improving the crystallinity and crystal orientation specificity for perovskites with a two-dimensional DJ-type structure.
[0031] More preferably, the carbon number of the alkyl group in the hydroiodide of the linear alkyl diamine in step S1 is 3-5.
[0032] Long alkyl chains can enhance the hydrophobicity of the film, but will affect the charge transport between the layers of the perovskite film. The role of the carbon number of the alkyl group in the hydroiodide of the linear alkyl diamine being less than 5 is to balance the charge transport and hydrophobicity of the perovskite film, and when the carbon number of the alkyl group is less than 3, the morphology of the perovskite material is close to three-dimensional, so the role of the additives lead chloride and formamidine chloride is reduced, the perovskite grains are smaller, and the film roughness is greater.
[0033] The present invention also protects a perovskite material prepared by the above-mentioned method for preparing the perovskite material.
[0034] The perovskite material prepared by the preparation method of the perovskite material provided by the present invention has lower roughness and larger grain size, which indicates that the perovskite material has excellent crystallinity and crystal orientation specificity.
[0035] The present invention also protects an application of the above perovskite material in perovskite solar cells.
[0036] The present invention also protects a perovskite solar cell, wherein the perovskite active layer is the above-mentioned perovskite material, and the specific structure of the perovskite solar cell is as follows: substrate / hole transport layer / perovskite active layer / electron transport layer / interface modification layer / metal electrode layer are stacked in sequence.
[0037] In a specific embodiment of the present invention, the substrate can be ITO, and ITO can also be used as the anode of the battery. A hole transport layer is added between the perovskite active layer and the anode as a spacer layer, and an electron transport layer and an interface modification layer are added between the perovskite active layer and the metal electrode layer, i.e., the cathode, so that during the operation of the perovskite solar cell, the holes in the photogenerated carriers can be transported to the anode through the hole transport layer for oxidation, and the electrons can be transported to the cathode through the electron transport layer and the interface modification layer for reduction. Among them, the interface modification layer can play a role in blocking hole transmission, avoiding the recombination of photogenerated electrons and holes at the cathode, thereby further improving the photoelectric conversion efficiency of the perovskite solar cell provided by the present invention.
[0038] In a specific embodiment of the present invention, the material of the interface modification layer may be BCP; the material of the electron transport layer may be PCBM; and the material of the hole transport layer may be PTAA.
[0039] Preferably, the thickness of the perovskite active layer is 250-300 nm.
[0040] Preferably, the thickness of the hole transport layer is 20-30 nm.
[0041] Preferably, the thickness of the electron transport layer is 30-40 nm.
[0042] Preferably, the thickness of the interface modification layer is 5 to 10 nm.
[0043] When the thickness of each functional layer is within the above preferred range, better interface contact and more efficient charge transfer can be achieved, so the perovskite cell provided by the present invention has a better photoelectric conversion efficiency.
[0044] In a specific embodiment of the present invention, before preparing the hole transport layer on the surface of the substrate, it is necessary to first use a plasma cleaning machine to perform surface treatment on the substrate.
[0045] In a specific embodiment of the present invention, the preparation process of the hole transport layer may include the following steps: taking 5 mg of PTAA and dissolving it in 1 mL of CB, and reacting it at 70°C for 3 hours to obtain a hole transport layer material; spin coating the hole transport layer material onto a substrate, and the spin coating conditions are spin coating at 5000 rpm for 30 to 40 seconds, and then annealing at 120°C for 5 minutes.
[0046] In a specific embodiment of the present invention, the preparation process of the perovskite active layer is the preparation process of the perovskite material, wherein the substrate that the perovskite material needs to rely on during the molding process is a hole transport layer; the specific operation of coating is spin coating, and the spin coating conditions are spin coating at a speed of 5000 rpm for 30 to 40 seconds, and then anti-solvent CB is added; the specific operation of annealing is annealing at 120°C for 10 minutes.
[0047] In a specific embodiment of the present invention, the preparation process of the electron transport layer may include the following steps: taking 20 mg of PCBM and dissolving it in 1 mL of CB, and reacting it at 70°C for 3 hours to obtain an electron transport layer material; spin coating the electron transport layer material onto the perovskite active layer, and the spin coating conditions are spin coating at 2000 rpm for 25 to 35 seconds, and then annealing at 60°C for 10 minutes.
[0048] In a specific embodiment of the present invention, the preparation process of the interface modification layer may include the following steps: taking 2 mg of BCP and dissolving it in 1 mL of isopropanol, and reacting it at 70°C for 3 hours to obtain the interface modification layer material; spin coating the interface modification layer material onto the electron transport layer, and the spin coating conditions are spin coating at 2000 rpm for 25 to 35 seconds.
[0049] In a specific embodiment of the present invention, the preparation process of the metal electrode layer may include the following steps: placing a perovskite solar cell having prepared a hole transport layer, a perovskite active layer, an electron transport layer and an interface modification layer into an evaporation device, with the interface modification layer facing downward; placing a metal in an evaporation boat for heating and evaporation, and finally allowing the metal electrode to be deposited on the interface modification layer.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] The present invention slows down the crystallization speed of two-dimensional perovskite through the synergistic effect of two additives, formamidine chloride and lead chloride, thereby enabling the crystal to grow fully, improving the crystallinity of the perovskite film and the specificity of the crystal orientation, and ultimately reducing the defects on the surface of the perovskite film. The roughness of the perovskite film prepared by the preparation method provided by the present invention is as low as 3.29nm, and the grain size D 50The maximum size can reach more than 200 nm, so that the photoelectric conversion efficiency of the perovskite solar cell prepared by using the perovskite material prepared by the present invention can reach up to 16.31%. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 Schematic diagram of the structure of a perovskite solar cell composed of the perovskite material prepared in Example 1 of the present invention.
[0053] Figure 2 This is an AFM image of the perovskite material prepared in Example 1 of the present invention.
[0054] Figure 3 This is a SEM image of the perovskite material prepared in Example 1 of the present invention.
[0055] Figure 4 GIWAXS images of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention, wherein the left image corresponds to the perovskite in Comparative Example 1, and the right image corresponds to the perovskite in Example 1.
[0056] Figure 5 It is a JV diagram of a perovskite solar cell composed of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention.
[0057] Figure 6 EQE diagram of the perovskite solar cell composed of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention.
[0058] Figure 7 This is a stability test diagram of a perovskite solar cell composed of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention.
[0059] Figure 8 This is a transient absorption diagram of a perovskite solar cell composed of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention.
[0060] Fig. 9 1 and 2 are XRD diagrams of the perovskite materials prepared in Comparative Example 1, Example 1 and Example 7 of the present invention. DETAILED DESCRIPTION
[0061] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0062] Example 1
[0063] A method for preparing a perovskite material comprises the following steps:
[0064] S1. adding organic amine hydroiodide, formamidine iodide and lead iodide to an organic solvent and mixing them thoroughly, adding formamidine chloride and lead chloride as additives, and mixing them thoroughly to obtain a perovskite precursor solution;
[0065] S2. coating the perovskite precursor solution obtained in step S1 onto a substrate and annealing to form a perovskite material;
[0066] The organic amine hydroiodide in step S1 is the hydroiodide of 1,4-butanediamine, and its molecular formula is (C4H8(NH3)2)I2, that is, the carbon number of the alkyl group is 4;
[0067] The molar ratio of formamidine chloride to lead iodide in step S1 is 0.1:1, and the molar ratio of formamidine chloride to lead chloride is 2:1, that is, the molar ratio of lead chloride to lead iodide in step S1 is 0.05:1.
[0068] Example 2
[0069] A method for preparing a perovskite material, which is different from Example 1 in that:
[0070] The organic amine hydroiodide in step S1 is the hydroiodide of 1,2-ethylenediamine, and its molecular formula is (C2H4(NH3)2)I2, that is, the carbon number of the alkyl group is 2.
[0071] Example 3
[0072] A method for preparing a perovskite material, which is different from Example 1 in that:
[0073] The organic amine hydroiodide in step S1 is the hydroiodide of 1,8-octanediamine, and its molecular formula is (C8H 16 (NH3)2)I2, that is, the carbon number of the alkyl group is 8.
[0074] Example 4
[0075] A method for preparing a perovskite material, which is different from Example 1 in that:
[0076] The organic amine hydroiodide in step S1 is the hydroiodide of butylamine.
[0077] Example 5
[0078] A method for preparing a perovskite material, which is different from Example 1 in that:
[0079] The molar ratio of formamidine chloride to lead iodide in step S1 is 0.06:1, and the molar ratio of formamidine chloride to lead chloride is 2:1, that is, the molar ratio of lead chloride to lead iodide in step S1 is 0.03:1.
[0080] Example 6
[0081] A method for preparing a perovskite material, which is different from Example 1 in that:
[0082] The molar ratio of formamidine chloride to lead iodide in step S1 is 0.15:1, and the molar ratio of formamidine chloride to lead chloride is 2:1, that is, the molar ratio of lead chloride to lead iodide in step S1 is 0.075:1.
[0083] Example 7
[0084] A method for preparing a perovskite material, which is different from Example 1 in that:
[0085] The molar ratio of formamidine chloride to lead iodide in step S1 is 0.1:1, and the molar ratio of formamidine chloride to lead chloride is 1:1, that is, the molar ratio of lead chloride to lead iodide in step S1 is 0.1:1.
[0086] Example 8
[0087] A method for preparing a perovskite material, which is different from Example 1 in that:
[0088] The molar ratio of formamidine chloride to lead iodide in step S1 is 0.1:1, and the molar ratio of formamidine chloride to lead chloride is 4:1, that is, the molar ratio of lead chloride to lead iodide in step S1 is 0.025:1.
[0089] Comparative Example 1
[0090] A method for preparing a perovskite material, which is different from Example 1 in that:
[0091] No lead chloride is added in step S1.
[0092] Comparative Example 2
[0093] A method for preparing a perovskite material, which is different from Example 1 in that:
[0094] In step S1, formamidine chloride is not added.
[0095] Comparative Example 3
[0096] A method for preparing a perovskite material, which is different from Example 1 in that:
[0097] The molar ratio of formamidine chloride to lead iodide in step S1 is 0.025:1, and the molar ratio of formamidine chloride to lead chloride is 1:1, that is, the molar ratio of lead chloride to lead iodide in step S1 is 0.025:1.
[0098] Comparative Example 4
[0099] A method for preparing a perovskite material, which is different from Example 1 in that:
[0100] The molar ratio of formamidine chloride to lead iodide in step S1 is 0.2:1, and the molar ratio of formamidine chloride to lead chloride is 0.5:1, that is, the molar ratio of lead chloride to lead iodide in step S1 is 0.4:1.
[0101] Comparative Example 5
[0102] A method for preparing a perovskite material, which is different from Example 1 in that:
[0103] The molar ratio of formamidine chloride to lead iodide in step S1 is 0.1:1, and the molar ratio of formamidine chloride to lead chloride is 0.5:1, that is, the molar ratio of lead chloride to lead iodide in step S1 is 0.2:1.
[0104] Comparative Example 6
[0105] A method for preparing a perovskite material, which is different from Example 1 in that:
[0106] The molar ratio of formamidine chloride to lead iodide in step S1 is 0.1:1, and the molar ratio of formamidine chloride to lead chloride is 8:1, that is, the molar ratio of lead chloride to lead iodide in step S1 is 0.0125:1.
[0107] Performance Testing
[0108] Roughness test of perovskite film: Use AFM analysis software to select the probe test area and obtain the root mean square roughness.
[0109] Perovskite grain size D 50 Test: The average particle size in the test area is obtained through TEM analysis software.
[0110] Preparation of perovskite solar cells: The perovskite materials prepared in the embodiments of the present invention and the comparative examples are used as the perovskite active layer to prepare perovskite solar cells. The specific structure of the cell is as follows: substrate / hole transport layer / perovskite active layer / electron transport layer / interface modification layer / metal electrode layer are stacked in sequence;
[0111] The material of the interface modification layer is BCP;
[0112] The material of the electron transport layer is PCBM;
[0113] The hole transport layer is made of PTAA;
[0114] The thickness of the hole transport layer is 25 nm, the thickness of the perovskite active layer is 275 nm, the thickness of the electron transport layer is 35 nm, and the thickness of the interface modification layer is 8 nm.
[0115] Photovoltaic conversion efficiency test: The JV performance test was carried out on the perovskite solar cells composed of the perovskite materials prepared by the embodiments of the present invention and the comparative examples. The cell chip test clip was connected to a Keithley 2400 source meter to measure the JV characteristics under the AM 1.5G spectrum of the solar simulator. The photoelectric conversion efficiency can be directly calculated from the obtained JV curve.
[0116] EQE test: EQE test was performed on the perovskite solar cells composed of the perovskite materials prepared by the embodiments of the present invention and the comparative examples, and the test results were obtained by using an integrated system (Enlitech, Taiwan, China) and a phase-locked amplifier with current pre-amplification under short-circuit conditions.
[0117] Stability test: The perovskite solar cells composed of the perovskite materials prepared by the embodiments of the present invention and the comparative examples were subjected to stability tests. The environmental stability test refers to placing the solar cell device in an environment with a relative humidity of 50%, and performing performance tests at regular intervals. The test steps are the same as the JV performance test mentioned above.
[0118] The specific test data are shown in Table 1. Figures 1 to 9 As shown:
[0119] Table 1. Performance test data of perovskite materials and corresponding batteries prepared in the examples and comparative examples
[0120]
[0121]
[0122] From the data of Examples 1 to 3 in Table 1, it can be seen that when the organic amine hydroiodide in step S1 is the hydroiodide of a linear alkyl diamine, when the alkyl carbon number is 3 to 5 (Example 1, the carbon number is 4), compared with the perovskite prepared by the organic amine hydroiodide with an alkyl carbon number of 2 (Example 2), the grains are larger and the film roughness is lower, so the photoelectric conversion efficiency is higher; and compared with the perovskite prepared by the organic amine hydroiodide with an alkyl carbon number of 3 (Example 3), the roughness of the perovskite film in Example 1 is relatively larger and the grains are relatively smaller, but the long alkyl chain between the perovskite layers in Example 3 will affect the charge transfer between the perovskite film layers, so the photoelectric conversion efficiency of the perovskite in Example 3 is lower. Example 4 uses the hydroiodide of a linear alkylamine to prepare the perovskite, and the obtained perovskite has a two-dimensional RP-type structure, while the perovskite in Example 1 uses the hydroiodide of a linear alkyl diamine as a preparation raw material and has a two-dimensional DJ-type structure. It can be seen from the data of Examples 1 and 4 that the preparation method of perovskite provided by the present invention has a better effect of improving the crystal quality of DJ-type two-dimensional perovskite, so the perovskite in Example 1 has a higher photoelectric conversion efficiency. It can be seen from the data of Examples 1, 5 to 8 that when the molar ratio of formamidine chloride to lead iodide in step S1 is (0.06 to 0.15): 1 and the molar ratio of formamidine chloride to lead chloride is (1 to 4): 1, the two additives of formamidine chloride and lead chloride added by the present invention can improve the particle size and roughness of the perovskite, and when the molar ratio of formamidine chloride to lead iodide is 0.1: 1, the particle size of the perovskite crystal is larger (Examples 5 to 7). From the data of Examples 1 and 7, it can be seen that when the molar ratio of formamidine chloride to lead chloride in step S1 is 2:1, the particle size of the perovskite crystal is larger and the film roughness is lower. This is because when the molar ratio of formamidine chloride to lead chloride is higher, the residual lead chloride in the system is less, and it is not easy to induce non-photoactive δ phase in the perovskite, which affects the crystallization of the perovskite. From the data of Comparative Examples 1 to 2, the two additives of formamidine chloride and lead chloride must be used together. From the data of Comparative Examples 3 to 6, when the molar ratio of formamidine chloride to lead iodide exceeds the range of (0.06 to 0.15):1, or the molar ratio of formamidine chloride to lead chloride is not in the range of (1 to 4):1, the crystal particle size of the obtained perovskite is smaller and the film roughness is also greater, indicating that the crystallinity of the perovskite is worse and the crystal orientation specificity is lower.
[0123] Figure 1 Schematic diagram of the structure of a perovskite solar cell composed of the perovskite material prepared in Example 1 of the present invention.
[0124] Figure 2 This is an AFM image of the perovskite material prepared in Example 1 of the present invention. Figure 2It can be seen that the perovskite film obtained in Example 1 of the present invention has lower roughness and a smoother surface.
[0125] Figure 3 This is a SEM image of the perovskite material prepared in Example 1 of the present invention. Figure 3 It can be seen that the perovskite film obtained in Example 1 of the present invention has larger grains and a denser surface.
[0126] Figure 4 GIWAXS images of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention, wherein the left image corresponds to the perovskite in Comparative Example 1, and the right image corresponds to the perovskite in Example 1. Figure 4 It can be seen that the perovskite film obtained in Example 1 of the present invention has a greater and stronger diffraction intensity (better crystallization) and a preferred orientation, indicating that the crystal orientation specificity is higher.
[0127] Figure 5 The JV diagram of the perovskite solar cell composed of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention. Figure 5 It can be seen that the perovskite film obtained in Example 1 of the present invention has higher open circuit voltage and short circuit current. Based on this, it can also be calculated that the perovskite film obtained in Example 1 of the present invention has a higher photoelectric conversion efficiency than the perovskite in Comparative Example 1, and also has a lower hysteresis effect.
[0128] Figure 6 EQE diagram of the perovskite solar cell composed of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention. Figure 6 It can be seen that the perovskite film obtained in Example 1 of the present invention has a better external quantum efficiency, indicating that the battery can efficiently realize photoelectric conversion.
[0129] Figure 7 The stability test diagram of the perovskite solar cell composed of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention. Figure 7 It can be seen that the perovskite film obtained in Example 1 of the present invention has better environmental stability and can maintain 95.1% of the original photoelectric conversion efficiency after being placed in an environment with a relative humidity of 50% for 600 hours.
[0130] Figure 8 Figure 1 is a transient absorption graph of a perovskite solar cell composed of the perovskite materials prepared in Comparative Example 1 and Example 1 of the present invention. Figure 8 It can be seen that the perovskite film obtained in Example 1 of the present invention has more excellent dynamic characteristics and better carrier lifetime.
[0131] Fig. 9The XRD diagrams of the perovskite materials prepared in Comparative Example 1, Example 1 and Example 7 of the present invention are shown in FIG. 1. In the XRD diagram of the perovskite material provided by the present invention, the intensity of the diffraction peak can be used to characterize the crystallization of the perovskite material. Fig. 9 It can be seen that the perovskite film obtained in Example 1 has stronger crystallization and better crystal orientation, and the ratio of the diffraction peak corresponding to the (202) crystal plane and the diffraction peak corresponding to the (111) crystal plane is close to 1, indicating that the crystallinity of the perovskite in Example 1 is close to 1. In Comparative Example 1, the intensities of the diffraction peak corresponding to the (202) crystal plane and the diffraction peak corresponding to the (111) crystal plane are both lower, and the ratio decreases, that is, the crystallinity decreases; the intensity of each diffraction peak in Example 7 is higher, indicating that the crystallization of the perovskite in Example 7 is better, but because the molar ratio of formamidine chloride to lead chloride in Example 7 is 1:1, the amount of lead chloride used is not optimal, so a non-photoactive δ phase is induced in the perovskite, reducing the crystallinity of the perovskite.
[0132] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a perovskite material, characterized in that: The specific steps include: S1, adding organic amine hydroiodide, formamidine iodide and lead iodide to an organic solvent and mixing them thoroughly, then adding formamidine chloride and lead chloride as additives, and mixing them thoroughly to obtain a perovskite precursor solution; S2, coating the perovskite precursor solution obtained in step S1 onto a substrate and annealing to form a perovskite material; In the step S1, the molar ratio of formamidine chloride to lead iodide is (0.06-0.15):1, the molar ratio of formamidine chloride to lead chloride is (1-4):1, and the molar ratio of lead chloride to lead iodide is (0.025-0.08):
1.
2. The method for preparing the perovskite material according to claim 1, characterized in that: In the step S1, the molar ratio of formamidine chloride to lead chloride is 2:
1.
3. The method for preparing the perovskite material according to claim 1, characterized in that: In the step S1, the organic amine hydroiodide is the hydroiodide of a linear alkyl diamine.
4. The method for preparing the perovskite material according to claim 3, characterized in that: The carbon number of the alkyl group in the hydroiodide of the linear alkyl diamine in step S1 is 3 to 5.
5. A perovskite material prepared by the method for preparing a perovskite material according to any one of claims 1 to 4.
6. Use of the perovskite material according to claim 5 in perovskite solar cells.
7. A perovskite solar cell, characterized in that: The perovskite active layer in the perovskite solar cell is the perovskite material according to claim 5, and the specific structure of the perovskite solar cell is as follows: substrate / hole transport layer / perovskite active layer / electron transport layer / interface modification layer / metal electrode layer are stacked in sequence.
8. The perovskite solar cell according to claim 7, characterized in that: The thickness of the perovskite active layer is 250-300 nm.
9. The perovskite solar cell according to claim 7, characterized in that: The thickness of the hole transport layer is 20-30 nm.
Citation Information
Patent Citations
X-ray direct detector and preparation method thereof
CN114361203A